Virtual courtroom - Edit Ómarsdóttir 1988-; Hafdís Sæland 1990-; Helga Margrét Ólafsdóttir 1990- (2019)
Sex crimes and aggravated assaults are some of the most difficult cases to be tried in court for everyone involved, especially for the victims taking the witness stand in unfamiliar and possibly threatening situations. Victims often experience a lot of anxiety during court proceedings which might affect greatly on their daily lives and their trial testimonies. Today, courtrooms are sketched up for the victims, seating arrangement is explained as well as the trial itself, to prepare them for the court proceeding. While this has helped to some extent, experts believe more could be done. Research have shown promising results of virtual reality in exposure therapies, being equally effective in treating fear compared to more conventional treatments. When it comes to the justice system, law enforcement is an example of profession that uses virtual reality in training, it has also been used to help law students train their legal skills. Based on promising results of using virtual reality in exposure therapies and training, and the need for a better preparation tool for victims of difficult crimes, a virtual courtroom could possibly be used to prepare victims of sex crimes before going to court. The Virtual Courtroom is an exact replica of courtroom 402 at the District Court of Reykjavík, often used in sex crime trials. It includes roles of those typically present in sex crime trials, i.e. a judge, a defender, the accused, a prosecutor, a legal counselor and a secretary. It offers the user the opportunity to walk around in the courtroom, sit down in the witness chair and introduce itself. The Virtual Courtroom is a new approach in the legal system to prepare victims of difficult crimes for court proceedings, possibly reducing anxiety that might occur. It has gotten positive feedback from domain experts who believe in promising results of using the Virtual Courtroom to prepare victims for court proceedings. Ein erfiðustu málin sem fara fyrir dóm eru kynferðisbrotamál en þau eru sérstaklega erfið fyrir þolendur ...